Mainstreaming Religious Moderation in Indonesian Higher Education: Perspectives on Goals, Curriculum Content, and Implementation Strategies - Muhamad Fauzi; Faisal; Jumhur; Mohammad Hilmy Baihaqy Yussof; Anis Malik Thoha; Muhammad Jhoni (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study maps stakeholder perspectives on the goals, content, and delivery strategies of Religious Moderation Education (RME) in Indonesian universities, and tests alignment between preferences and current practice. It responds to policy calls to move beyond course‑only provision toward campus‑wide mainstreaming. Design/methods/approach – A cross‑sectional online survey of 500 respondents (200 lecturers, 300 students) from public and Islamic universities used structured Likert‑type questionnaires. Data were analyzed using descriptive statistics and cross‑tabulations. Findings – Respondents strongly endorsed core objectives: strengthening Pancasila‑based civic identity (85%), preventing conflict and radicalism (84%), and bridging religious–non‑religious perspectives (80%). Content priorities centred on interfaith harmony (M = 4.35) and civic‑constitutional values (M = 4.28), with intra‑Islam harmony also high (M = 4.12). Integrated cross‑curricular models received the highest effectiveness rating (M = 4.32) yet were less used than IRE‑only courses (41% vs 68%); campus‑culture programming was also effective (M = 4.05; usage 55%). These figures indicate a misalignment between stakeholder preferences and prevailing practice. Research implications/limitations – Evidence supports system‑level integration of RME across curricula and campus culture, coupled with lecturer development and assessment. Cross‑sectional, self‑report data limit causal inference and generalizability; longitudinal and implementation studies are needed. Originality/value – Provides a large‑N, multi‑stakeholder baseline and advances a goals–content–strategy framework not only as a practical policy tool but also as a conceptual contribution to the study of Religious Moderation Education (RME) and contemporary religious education more broadly. By analytically linking normative goals, curricular content domains, and delivery strategies, the framework offers a transferable lens for examining how religious education can balance identity formation with civic pluralism. It also guides institutional audits and policy design for inclusive, effective RME and underscores the need for system-level reforms to enhance the civic and pluralistic impact of religious education in diverse societies